ELECTROPHORETIC STUDY ON MUSCLE AND EYE LENS PROTEINS OF THREE SCIAENIDS - Chakraborty, Sushant Kumar (Indian Journal of Fisheries, 2011)
Results of the electrophorctic study on muscle and eye lens proteins of three species of scianeids viz.Johnius macrorhynus (Mohan), Johnieops wgleri (Blocker) and Otolithes cuvieri (Trewavas) is reported in thepresent communication. The number of protein fractions in the muscle of/, vogleri,}. macrorhynus andO. cuvieri were found to be 10, 11 and 14 respectively while the same for eye lens proteins as revealedby the densitometric scan were 10 for /. vogleri and 6 each for /. macrorhynus and O. cuvieri respectively.The staining pattern of the muscle proteins shows that it was more intense for fraction 4, 8, 10 and 11for /. vogleri, 6,7,9, and 10 for /. macrorhynus and 1,3,11 and 13 for O. cuvieri. In case of eye lens proteinsthe staining was more intense for fractions, 1, 3, 7, and 8 for /. vogleri, 1, 4, 5 and 6, for /. macrorhynusand 1,2,4 and 6 for O. cuvieri. The differences in the number of protein fractions, their mobility patternand staining intensity indicates species specificity.